Pengembangan Kawasan Ekowisata di Sekitar Danau Paniai Distrik Paniai Timur Kabupaten Paniai - Anfred Yeimo; Lazarus Ramandei; Sudiro Sudiro (Lembaga Pengembangan Kinerja Dosen, 2024)
This research aims to identify the potential of the Paniai Lake ecotourism area as a natural tourist attraction that needs to be improved and developed, because it has very unique natural, socio-cultural and historical conditions. The potential tourist areas in Paniai Lake include Yautogi Hill, Bobaigo Hill and Aikai Pier. The three tourism potentials in the Paniai Lake area have huge opportunities to be developed as tourist destinations. The method used in this research is a qualitative method, namely using interview and observation methods with specific aims and uses. To achieve this goal requires a method that is relevant to the goals to be achieved and includes research procedures and techniques. By using interview and observation methods as well as SWOT analysis to obtain Strengths-Opportunities, Weaknesses-Threats. The results show that the ecotourism potential of the ecotourism area in Paniai Lake includes, Yautogi Hill, Bobaigo Hill, and Aikai Pier, the three tourism potentials in the Paniai Lake area have very large opportunities to be developed as tourist destinations, apart from having potential that can be developed, the third This destination has a very unique history and culture which is a special attraction for the development of the tourism area around Lake Paniai, as well as involving community participation in tourism development around Lake Paniai to improve the economy of the local community.